Eternity Descending into Time: Badiou and the Cinematic Temporality of Love - Lu Zeng (Film-Philosophy)
This article brings Alain Badiou’s philosophy of love and truth into the consideration of the cinematic real. It argues that love has been overlooked in the discourse of the cinematic real and that love should be recuperated in and for cinema so that a version of the cinematic real informed by Badiou’s philosophy can emerge. Differing from the Althusserian–Lacanian concept of the real or reality, Badiou’s version of the cinematic real is infused with intensity and contingency; it accommodates love and endorses cinephilia. For Badiou, the temporality of love and any truth-procedure is one of eternity descending into time, which can roughly be understood as an affective experience of sensing the presence of eternity in fleeting moments. Specifically, this article explores how Badiou’s truth manifests in cinema through a temporality of love using examples from Mauvais Sang (Leos Carax, 1986) and In the Mood for Love (Wong Kar Wai, 2000).